Complications and outcomes of curettage, chemical cauterization and bone graft in giant cell tumor of bone - Alam, M. Shariful; Hossain, Monaim; Biswas, Pathik; Hasan, Rakibul; Mahmud, M. Jobayer Al; Kabir, Humayun (International Journal of Research in Orthopaedics, 2025)
Background: Giant cell tumor of bone (GCTB) is a locally aggressive benign bone neoplasm with a high potential for recurrence. While intralesional curettage remains the standard treatment, combining chemical cauterization and bone grafting may enhance therapeutic outcomes. This study aimed to evaluate the complications and outcomes of this combined approach in managing GCTB. Methods: A prospective observational study was conducted at the national institute of traumatology and orthopedic Rehabilitation (NITOR), Dhaka, Bangladesh, from September 2021 to March 2024. A total of 32 patients diagnosed with GCTB were treated using curettage, chemical cauterization and bone grafting. Functional outcomes were assessed using the Musculoskeletal Tumor Society (MSTS) scoring system, while complications and recurrence rates were recorded. Statistical analysis was performed using Student’s t-test and Chi-square test, with significance set at p<0.05. Results: The mean MSTS score significantly improved from 58.8%±15.4% preoperatively to 85.2%±15.9% at the last follow-up (p<0.01). A low recurrence rate of 6.25% was observed. Pain levels, assessed by the visual analogue scale (VAS), significantly decreased from 4.3±1.2 to 2.1±1.5 (p=0.00002). Complications included joint stiffness (25%), superficial infections (9.38%) and early osteoarthritis (6.25%). Conclusions: The combination of curettage, chemical cauterization and bone grafting proved to be an effective treatment strategy for GCTB, resulting in low recurrence, significant pain reduction and favorable functional outcomes. This approach should be considered a reliable management option, particularly in resource-limited settings.